(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the scientific and practical contributions of the female astrolabe maker referred to in the historical sources as al-ʿIjliya and widely known in modern literature as Maryam al-Usturlabi. Drawing primarily on the tenth century bio-bibliographical work Al-Fihrist by Ibn al-Nadim, and situating its evidence within the broader history of the astrolabe and of astronomy in Islamic civilization, the study reconstructs the intellectual and courtly environment in which she worked at the court of the Hamdanid emir Sayf al-Dawla in Aleppo. The article examines the Greek origins and Islamic development of the astrolabe, its construction and its religious and practical functions, the place of women in the scientific culture of medieval Islam, and the documentary basis for what can responsibly be said about al-ʿIjliya herself. It argues that, although the surviving record concerning her is extremely limited, her recognized mastery of one of the most demanding of the mathematical crafts marks her as a figure of genuine historical importance and as an enduring symbol of the participation of women in science.